2004
DOI: 10.1002/mabi.200400067
|View full text |Cite
|
Sign up to set email alerts
|

Local Chain Mobility of Gellan in Aqueous Systems Studied by Fluorescence Depolarization

Abstract: The local chain mobility of a gellan, an electrolyte polysaccharide, in aqueous systems was examined with respect to the effect of the temperature, the concentration of gellan (c(G)), and the concentration of added salt (c(S)). The relaxation time of local motion was estimated for fluorescein isothiocyanate (FITC)-labeled-gellan by the fluorescence depolarization technique, and the chain mobility was discussed. The relaxation time increased with decreasing temperature, in particular when accompanying the coil-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…However, the cation species coexisting with pectin chains in an aqueous solution have no effect on the chain mobility. Recently, similar results have been obtained for gellan 16 sthe chain mobility of the random-coiled gellan in aqueous solutions was not affected by the addition of a cation species, although the coil-helix transition temperature as well as the gelation temperature for gellan changed with the concentration of the cation species. These results imply that cation species do not affect the chain mobility of anionic polysaccharides.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…However, the cation species coexisting with pectin chains in an aqueous solution have no effect on the chain mobility. Recently, similar results have been obtained for gellan 16 sthe chain mobility of the random-coiled gellan in aqueous solutions was not affected by the addition of a cation species, although the coil-helix transition temperature as well as the gelation temperature for gellan changed with the concentration of the cation species. These results imply that cation species do not affect the chain mobility of anionic polysaccharides.…”
Section: Resultssupporting
confidence: 78%
“…The labeling reaction was assessed using fluorescence techniques. 16 We compared the fluorescence spectra as well as r j between an aqueous solution of labeled-pectin and an unlabeled pectin containing a trace of free An-MeOH. The fluorescence spectrum for the solution of labeled-pectin was 5 nm red-shifted from that for the solution of unlabeled pectin while maintaining the fingerprint characteristics of the anthryl group.…”
Section: Methodsmentioning
confidence: 99%
“…The sample concentrations used in the present study were selected based on a previous study by Nickerson and Paulson (2004) who found C * at 25°C for gellan solutions to be 0.44% (w/w) in the absence of added ions, and 0.25% (w/w) and 0.20% (w/w) in the presence of added K + (0.5 mM) and Ca 2+ (0.25 mM), respectively. Values were comparable to those determined by Nickerson, Paulson, and Speers (2003) and Horinaka, Kani, Honda, Uesaka, and Kawamura (2004) for similar systems. Overlap concentrations were lower than critical gelation concentrations determined using percolation theory corresponding to levels of 0.77% (w/w) for samples without added salts, and 0.42% (w/w) and 0.28% (w/w) with added K + (0.5 mM) and Ca 2+ (0.25 mM), respectively.…”
Section: Methodssupporting
confidence: 76%
“…6, also shows increased emission in the exposed areas. The increase in the observed intensity at the exposed areas was $2.3 times (¼ G Q , eqn (12)) that outside of the areas (Fig. 6a).…”
Section: Influence Of Nanostructured Silver Regions On Fitc Fluorescencementioning
confidence: 81%
“…7,10,11 Cations help to crosslink gellan's negatively charged polysaccharide helices, forming helix-helix aggregates. 6 Most work has made use of rheology to monitor changes in the bulk viscosity, although there is a report of fluorescence anisotropy employed to monitor chain conformation, 12 as well as calorimetry. 13 Previously we have made use of changes in the fluorescence lifetime of a hydrophilic probe, DASPMI (4-(4-(dimethylamino)styryl)-N-methyl-pyridiniumiodine) to elucidate this viscosity variation.…”
Section: Introductionmentioning
confidence: 99%